2021
DOI: 10.1016/j.jtho.2021.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Origins of Local and Distant Metastases in Lung Cancer

Abstract: Introduction: Metastasis is the primary cause of lung cancer-related death. Nevertheless, the underlying molecular mechanisms and evolutionary patterns of lung cancer metastases are still elusive.Methods: We performed whole-exome sequencing for 40 primary tumors (PTs) and 61 metastases from 47 patients with lung cancer, of which 40 patients had paired PTs and metastases. The PT-metastasis genomic divergence, metastatic drivers, timing of metastatic dissemination, and evolutionary origins were analyzed using ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…), CNA. pairs, including only 7 brain metastases [11]. The increased frequency of KRAS mutations is not unique to LUAD with brain metastases.…”
Section: Discussionmentioning
confidence: 86%
“…), CNA. pairs, including only 7 brain metastases [11]. The increased frequency of KRAS mutations is not unique to LUAD with brain metastases.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have revealed that primary metastases had various levels of genomic heterogeneity to distinct tumor migration patterns ( 35 ). Related genes were enriched in different metastatic locations, which would alter tumor microenvironment and related inflammatory cell distribution and finally influence the response to ICIs ( 28 , 29 ). The presence of liver metastases (LMs) is associated with lower prognosis in immunotherapy compared to metastases in other organs ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional views suggest that SBRT to single-site lesion was enough, but there were recent concerns that question whether multisite therapy was superior to single lesion therapy ( 43 ). Due to the organs’ own specific heterogenetic tumor-associated antigens, multisite SBRT may broadly enhance the outcome of immunotherapy by facilitating more antigen released ( 28 , 44 ). Apart from the number of sites to be verified by prospective clinical trials, the localization of SBRT combined with ICIs also remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For total genetic alterations, Tang et al . [ 9 ] revealed that the overall concordance between primary tumors (PT) and metastatic tumors (MT) was 45.6%, and it ranged from 7.3% to 80.6% per patient. Furthermore, metastatic site‐specific differences were also observed.…”
Section: Introductionmentioning
confidence: 99%